2020
DOI: 10.1590/0074-02760200140
|View full text |Cite
|
Sign up to set email alerts
|

Lipophosphoglycans from dermotropic Leishmania infantum are more pro-inflammatory than those from viscerotropic strains

Abstract: Although Leishmania infantum is well-known as the aethiological agent of visceral leishmaniasis (VL), in some Central American countries it may cause atypical non-ulcerated cutaneous leishmaniasis (NUCL). However, the mechanisms favoring its establishment in the skin are still unknown. Lipophosphoglycan (LPG) is the major Leishmania multivirulence factor involved in parasite-host interaction. In the case of viscerotropic L. infantum, it causes an immunosuppression during the interaction with macrophages. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…For example, Leishmania infantum (viscerotropic) can cause cutaneous lesions in Honduras, Central America. (32) Leishmania donovani, another viscerotropic species, can cause unusual dermal lesions after therapeutic failure known as Post-kala-azar dermal Leishmaniasis (PKDL). (33) The opposite is also true for Leishmania amazonensis (dermotropic).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Leishmania infantum (viscerotropic) can cause cutaneous lesions in Honduras, Central America. (32) Leishmania donovani, another viscerotropic species, can cause unusual dermal lesions after therapeutic failure known as Post-kala-azar dermal Leishmaniasis (PKDL). (33) The opposite is also true for Leishmania amazonensis (dermotropic).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study documented that the structural polymorphism of LPG from L. infantum and L. braziliensis trigger the stimulation of host cells via Toll-like receptors (TLRs) [ 35 ]. In addition, other previous studies revealed that the LPG of dermotropic strains caused by L. infantum , which are devoid of side chains, triggers the higher production of cytokines and nitric oxide (NO) levels in comparison with that of viscerotropic strains, whereas LPGs target the immunosuppression by interaction with macrophages [ 42 , 43 , 44 ]. On the other hand, LPGs play a pro-inflammatory role during the infection by L. amazonensis and L. braziliensis .…”
Section: Virulence Factors Of Leishmaniamentioning
confidence: 99%
“…LPGs from viscerotropic/dermotropic L. infantum possess three types of LPG: (I) without side chains, (II) with one β‐glucose linked to the repeat units, and (III) with two to three β‐glucoses as side chains. Those polymorphisms did not affect sand fly development but affected NO/cytokine production by murine macrophages (Cardoso et al, 2020 ; Coelho‐Finamore et al, 2011 ; Soares et al, 2002 ). Like L. infantum , Leishmania braziliensis LPGs from different clinical forms also displayed unbranched and branched sugars in their repeat units.…”
Section: Introductionmentioning
confidence: 99%